A simplified method to estimate Diphyllobothrium spp. infection in salmonids - Kuhn, Jesper A.; Knudsen, Rune; Kristoffersen, Roar; Amundsen, Per-Arne (Journal of Fish Diseases, 2016)
This is the peer reviewed version of the following article: Kuhn, J.A., Knudsen, R., Kristoffersen, R. & Amundsen, P.A. (2017). A simplified method to estimate Diphyllobothrium spp. infection in salmonids. Journal of Fish Diseases, 40(7), 863-871., which has been published in final form at https://doi.org/10.1111/jfd.12566 . This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions for Self-Archiving. Some fish parasites constitute severe management problems as they may cause mortality of their fish host or are important zoonoses of humans. Parasite assessments are therefore critical to keep track of infections. If conventional sampling techniques can be simplified, parasite assessments might be easier to obtain, less time-consuming and more extensive. In this study, we compare the assessed number of Diphyllobothrium spp. cysts (CYST) with the counted number of Diphyllobothrium spp. plerocercoid larvae recovered using a conventional digestive technique (LARV). The aim was to determine the potential of using CYST as a simplified methodology for assessing Diphyllobothrium spp. infection in salmonids. In total, 365 brown trout and 424 Arctic charr were sampled from nine lakes in subarctic Norway. Strong correlation, significant linear relationship and large amount of explained variation were found between log10CYST and log10LARV in both fish species. The method had a slight, but not significant tendency to work better in charr compared to trout. In addition, absolute difference between CYST and LARV increased at parasite intensities >100 indicating that the method has reduced functionality when estimating parasite intensity in heavily infected salmonid populations. However, overall, using this simplified and less time-consuming methodology, a good indication of Diphyllobothrium spp. intensity, abundance and prevalence was obtained. We suggest that this method provides a sound proxy of the Diphyllobothrium spp. burden and have the potential to be used in parasite ...